Aging‐related anatomical and biochemical changes in lymphatic collectors impair lymph transport, fluid homeostasis, and pathogen clearance. Issue 4 (15th May 2015) - Zolla, Valerio; Nizamutdinova, Irina Tsoy; Scharf, Brian; Clement, Cristina C.; Maejima, Daisuke; Akl, Tony; Nagai, Takashi; Luciani, Paola; Leroux, Jean‐Christophe; Halin, Cornelia; Stukes, Sabriya; Tiwari, Sangeeta; et al.
Summary The role of lymphatic vessels is to transport fluid, soluble molecules, and immune cells to the draining lymph nodes. Here, we analyze how the aging process affects the functionality of the lymphatic collectors and the dynamics of lymph flow. Ultrastructural, biochemical, and proteomic analysis indicates a loss of matrix proteins, and smooth muscle cells in aged collectors resulting in a decrease in contraction frequency, systolic lymph flow velocity, and pumping activity, as measured in vivo in lymphatic collectors. Functionally, this impairment also translated into a reduced ability for in vivo bacterial transport as determined by time‐lapse microscopy. Ultrastructural and proteomic analysis also indicates a decrease in the thickness of the endothelial cell glycocalyx and loss of gap junction proteins in aged lymph collectors. Redox proteomic analysis mapped an aging‐related increase in the glycation and carboxylation of lymphatic's endothelial cell and matrix proteins. Functionally, these modifications translate into apparent hyperpermeability of the lymphatics with pathogen escaping from the collectors into the surrounding tissue and a decreased ability to control tissue fluid homeostasis. Altogether, our data provide a mechanistic analysis of how the anatomical and biochemical changes, occurring in aged lymphatic vessels, compromise lymph flow, tissue fluid homeostasis, and pathogen transport.